2018
DOI: 10.1186/s40035-018-0119-7
|View full text |Cite
|
Sign up to set email alerts
|

Adjunct rasagiline to treat Parkinson’s disease with motor fluctuations: a randomized, double-blind study in China

Abstract: BackgroundThe use of adjunct rasagiline in levodopa-treated patients with Parkinson’s disease and motor fluctuations is supported by findings from large-scale clinical studies. This study is to investigate the efficacy and safety of adjunct rasagiline in Chinese patients with Parkinson’s disease, as a product registration study.MethodsThis 16-week, randomized, double-blind, parallel-group, multicenter, placebo-controlled study of rasagiline 1 mg/day included levodopa-treated patients with Parkinson’s disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Hypokinesia of limb and trunk movements were not improved in this study indicating the beneficial effect exerted by selegiline add-on therapy was not by dopaminergic pathway [70]. Rasagiline, as an effective monotherapy in early PD and add-on therapy in PD patients with motor fluctuations [71,[104][105][106], has also been studied on FOG. In the LARGO study [71], a prospective, double-blind, randomized, placebo-controlled study enrolled 687 PD patients, in which 278 patients had FOG.…”
Section: Monoamine Oxidase B Inhibitors (Mao-b Inhibitor)mentioning
confidence: 64%
“…Hypokinesia of limb and trunk movements were not improved in this study indicating the beneficial effect exerted by selegiline add-on therapy was not by dopaminergic pathway [70]. Rasagiline, as an effective monotherapy in early PD and add-on therapy in PD patients with motor fluctuations [71,[104][105][106], has also been studied on FOG. In the LARGO study [71], a prospective, double-blind, randomized, placebo-controlled study enrolled 687 PD patients, in which 278 patients had FOG.…”
Section: Monoamine Oxidase B Inhibitors (Mao-b Inhibitor)mentioning
confidence: 64%
“…No studies have specifically examined and manifested the efficacy, tolerability and safety of rasagiline monotherapy in Chinese patients with PD, although the efficacy of rasagiline administration as adjunct therapy to levodopa in this population has been confirmed [ 14 , 15 ]. Therefore, this randomized, double-blind, parallel, placebo-controlled, fixed-dose study aimed to evaluate the efficacy and safety of rasagiline in Chinese patients with early PD not treated with levodopa.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse events related to the drug completely disappeared after withdrawal. Comparing the results of safety analysis of this study to those of other clinical trials investigating other rasagiline-containing products[7] [10][31] concerning frequency and severity of adverse events, the safety profile of Ralago ® seems to be somewhat better. As PD usually occurs in the older population which is more prone to be affected by side effects of pharmacotherapy because of polimorbidity and drug interactions, antiparkinsonian medications with higher safety should be preferred in these patients.…”
mentioning
confidence: 76%
“…Furthermore, Ralago ® also appears to own the previously described ability of rasagiline to beneficially influence the severity of NMS in PD[12] [13]. Some previous studies have found that rasagiline may improve HRQoL[7] [31]. By alleviating symptoms reported to be the main sources of disability and distress in everyday life (fatigue, bradykinesia, and tremor), Ralago ® may also be able to improveHRQoL.The safety profile of the product can also be considered very good.…”
mentioning
confidence: 90%